Effect of long-acting progesterone administration after natural mating on gestation in llamas of the argentinean Puna - Abalos, Marcos C. (2022)
The aim of this work was to evaluate the effects of long-acting progesterone (LAP4) administered in the early stages of gestation on plasma P4 concentration and pregnancy and embryonic / fetal mortality rates between 30 and 60 days of gestation. Adult females (n = 92) with the presence of an ovarian follicle >7 mm were naturally mated with males of proven fertility (day -2). At day 0, ovarian ultrasonography was performed to confirm the occurrence of ovulation. On day 2, females that ovulated were assigned to receive a dose of 50 mg IM of LAP4 (LAP450, n = 26), 100 mg of LAP4 (LAP4100, n = 22), or 5 ml of saline (Control, n = 25). Pregnancy diagnosis and gestational losses were determined by ultrasonography at 30 and 60 days of gestation. Blood samples were collected on days 0, 3, 7, 10 and 14 after ovulation to determine the plasma P4 concentration by microparticle chemiluminescence (CMIA). No significant differences were observed in the pregnancy rate between the three groups at day 30 (p = 0.20) and at day 60 (p = 0.28). The embryonic mortality rates were not different (p = 0.86) between groups (LAP450 = 10%, LAP4100 = 5.5% and Control = 6.6%). A higher (p <0.05) plasma P4 concentration was determined in llamas that received 100 mg of LAP4 than those recorded in the other two groups on days 3 and 7 after ovulation; however, there were no differences between groups on days 10 and 14. The study results do not support the hypothesis that administration of LAP4 in the early stages after ovulation increases the pregnancy rate or decreases embryonic / fetal mortality in llamas.